Enhancing Small and Medium Enterprises (SMEs) in a Globalized and Innovative Economy: Challenges and Opportunities - Enaifoghe, Andrew (Rescollacom (Research Collaborations Community), 2024)
This article explores Small and Medium Enterprises (SMEs) in a globalized and innovative economy, looking specifically at the challenges and opportunities. The establishment and expansion of new firms provide a sizable amount of net new jobs. While high-expectation entrepreneurial enterprises and gazelles are usually found among innovative and technology-based new organizations, it is also essential that there be a sizable supply for them to play a significant part in economic growth. In other words, encouraging all forms of entrepreneurship is likely to increase the number of innovative, fast-growing enterprises as well as entrepreneurship. In many European countries, entrepreneurship needs to be encouraged. Findings show the crucial role the SME sector plays in the South African economy in tackling sustainable development. About 90% of all official firms in South Africa are thought to be small, medium, or micro-enterprises. The study concluded that one of the major contributions to the South African economy is the SME sector. The SME is not just viewed as a source of new jobs, but also as a sector that absorbs laid-off workers from both the private and public sectors.